The Comparison Level of Entrepreneurial Intention and Creative Thinking Skills Among Polytechnics Students in Malaysia - Sri Sumarwati,; Setiyani,; Amiruddin, Mohd Hasril; Madar, Ahmad Rizal (Online Journal for TVET Practitioners, 2022)
The Malaysian government's aims to entrepreneurship are one of the problems solved to reducing the unemployment rate. This study aims to identify entrepreneurship and creative thinking skills among polytechnic students in Malaysia. Respondents in this quantitative study consisted of students from Polytechnic Ungku Omar (PUO), Polytechnic METrO Kuala Lumpur (PMKL), Polytechnic METrO Johor Bahru (PMJB), Polytechnic Mersing Johor (PMJ), Polytechnic Melaka (PMK), Polytechnic Sultan Mizan Zainal Abidin (PSMZA), Polytechnic Merlimau Melaka (PMM), Polytechnic Banting (PBS) and Polytechnic Port Dickson (PPD). The respondents were selected using a purposive stratified random sampling method. The research instrument consists of 36 items, namely: demographic, creative thinking skills, and entrepreneurship intention. Statistical tests used in this research include frequency, percentage, and t-test. The data were analyzed using Statistical Package for the Social Science (SPSS) version 21. Findings show that male students are more entrepreneurial and creative than female students. This research also found a significant difference between engineering and non-engineering polytechnic students in the level of entrepreneurial tendency. Furthermore, engineering students have a moderate level, while non-engineering students have a low level of creative thinking skills. These results also obtained that exposure to entrepreneurial careers, according to non-formal training does not necessarily affect a student's tendency to become an entrepreneur. The ingenuity and creativity of a student in a subject while studying may be an opportunity and an idea to start a business. Initial awareness of entrepreneurship through exposure to entrepreneurship during the study should be applied to reduce the risk of failure in entrepreneurship start-ups.